Determinats of Excess Liquidity in Tanzanian Commercial Banks - Aikaeli, Jehovaness; University of Dar es Salaam (Dar es Salaam Dar es Salaam University Press, 2011)
Among the current concerns in Tanzania is that banks are awash with liquidity notwithstanding the private sector high demand for credit. Excess liquidity constrains banks? productivity/efficiency; and on the other hand, strangles the share of credit allocated to the private sector, thereafter upsetting economic growth. To determine the causes of excess liquidity, autoregressive distributed lag model is employed. The findings suggest that high cost of funds, credit risks, volatility of deposit holders? cash preference, inter alia, perpetuated accumulation of excess liquidity in commercial banks. Important policy implications on price stability, risks minimization, proper supervision and optimal liquidity management are highlighted
Keywords: Excess Liquidity